STRUGGLE FOR SURVIVAL IN LEWIS CARROLL ALICE’S ADVENTURE IN WONDERLAND - Longkutoy, Della; Rorintulus, Olga; Mamentu, Agustine C. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
In this study, the writer focuses the analysis about the survival because survival is related in human life. The important thing is the human need survive to struggle something in their life. When the people in a difficult situation, they can learn many things to face and solve the problem or obstacle in their life. They can get a motivation and idea what will they do to get the purpose. So, it can be useful for people to do the survival., To reveal Alice’s obstacles in the adventure., To reveal Alice’s efforts to overcome her obstacles for struggle survival., After doing the research, the writer expects the reader can understand the message of Alice in the wonderland Novel and learn about the adventure of survival in it. In conducting the research, the writer used qualitative research because the data are collected in the form of words. Qualitative research is descriptive. The data obtained are in the form of words or picture rather than number., In conducting this research, the writer divided the sources into two categories, the primary and secondary sources. Primary source is novel The Alice’s Adventure in the Wonderland and secondary sources are the related books that support the study and the data from internet, In analysing the data, the writer used objective approach. This study will focuses on the work itself. Alice''s Adventures in Wonderland represents the child''s struggle to survive in the confusing world of adults. In this novel, Alice follows a talking White Rabbit, down a well, through a pool of tears, and into a garden where she encounters a Mad Hatter’s tea party, a game of croquet played with living things, and a trial of the Knave of Hearts. Alice is a child entering a world of adults ranging from the neurotic White Rabbit, to the officious Duchess and psychopathic Queen of Hearts., While in Wonderland, Alice is confronted with more than the questioning of who she is and whether she is still the same person she was when she woke up in the morning.